High-dynamic wavelength tracking and millimeter-level ranging inter-satellite laser communication link with feedback-homodyne detection - Tian, Yang; Zhong, Jie; Lin, Xiaoxiang; Xiao, Pei; Yang, Haifeng; Zhong, Yu; Kang, Dongpeng (Applied optics. Optical technology and biomedical optics, 2019)
The Integrated Laser Communication/Ranging System, which uses a coded signal as the ranging information carrier, is of great importance to the next large-capacity inter-satellite information network. In this paper, a system design with a high-sensitivity feedback-homodyne detection scheme and an asynchronous ranging algorithm is demonstrated with real-time field-programmable gate array-implementation (FPGA). The parallel fast Fourier transformation (FFT) estimation is applied to improve the speed and the range of the wavelength drift tracking, which can handle a dynamic wavelength drift up to 2.4 pm/s (300 MHz/s). Meanwhile, for clock sources with subtle dynamic frequency offset and sufficient stability, the proposed fractional symbol ranging method is proven to achieve millimeter-level measurement accuracy. The designed system is shown to perform well in terms of both laser linewidth tolerance and noise resistance.